WTP Analysis of BPJS Health Contributions for Informal Workers in Indonesia: Literature Study - Adinda, Faiza; Octavelia, Anggi Tri; Dany, Cut Nasywa Kesuma; Gurning, Fitriani Pramita (PROMOTOR, 2024)
Health issues are an aspect that always receives major attention both nationally and internationally. Currently, the Indonesian government is focusing on the BPJS Health program to achieve the UHC target of 98% in 2024. However, the number of participants recorded at the end of 2023 was 95.88% so it has not yet reached the UHC target. Apart from that, problems also emerged related to the BPJS Health budget deficit caused by participants who were in arrears and did not pay their BPJS Health contributions. Based on BPJS Health data, there was an increase in the number of BPJS participant arrears in August 2023 amounting to 15.73 million coming from the informal worker sector so in this case researchers are interested in analyzing the determinants that influence willingness to pay BPJS contributions in Indonesia. This research uses literature study methods sourced from Google Scholar, PubMed, Connected Paper, and Publish or Perish and several official health sites. This research shows that there are 10 determinants that influence WTP towards BPJS Health contributions, namely, education, knowledge, employment, income, perception, quality of health services. Payment facilities are difficult to access, expenditure on essential and non-essential food, number of family members, and history of illness. The most dominant determinant of WTP for BPJS Health contributions is the income of informal workers where the income earned per month is low or irregular so that informal workers prioritize meeting their daily needs rather than having to pay BPJS Health contributions.